2017
DOI: 10.7861/clinmedicine.17-2-143
|View full text |Cite
|
Sign up to set email alerts
|

Paradoxical reaction in the form of pleural effusion after onset of anti-tuberculous medication for tubercular lymphadenitis

Abstract: We present the case of a 26-year-old Indian male who developed pleural effusion while undergoing treatment for tuberculous lymphadenitis. We describe the work-up for his condition and how he was managed. The possibility of development of a paradoxical reaction in the form of pleural effusion after initiation of anti-tuberculous therapy has to be kept in mind while treating such patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…According to the relevant literature, when diagnosis of TL is established and adequate anti-TB regimen is administered, a relapse in adenitis or appearance of draining sinuses could be expected and managed by adding oral steroids along with the anti-TB medication [32], despite steroids not being prescribed for TL treatment [34], except for local discomfort [20]. The use of corticosteroids while receiving therapy for TL seems to resolve paradoxical reaction and improves the clinical outcome [30, 3539]. Although steroids seem to be particularly effective against paradoxical reaction during appropriate treatment for intracranial tuberculomas [21, 32], TB meningitis [40], and pleural TB [41], another study showed no significant clinical response [42].…”
Section: Discussionmentioning
confidence: 99%
“…According to the relevant literature, when diagnosis of TL is established and adequate anti-TB regimen is administered, a relapse in adenitis or appearance of draining sinuses could be expected and managed by adding oral steroids along with the anti-TB medication [32], despite steroids not being prescribed for TL treatment [34], except for local discomfort [20]. The use of corticosteroids while receiving therapy for TL seems to resolve paradoxical reaction and improves the clinical outcome [30, 3539]. Although steroids seem to be particularly effective against paradoxical reaction during appropriate treatment for intracranial tuberculomas [21, 32], TB meningitis [40], and pleural TB [41], another study showed no significant clinical response [42].…”
Section: Discussionmentioning
confidence: 99%
“…1 The common clinical manifestation of PR includes recurring symptoms such as fever, cough and polypnea, radiological deterioration, appearance of pleural effusion or ascites, new intracranial tuberculosis and the progression of lymphadenitis. 2 PR can occur from one week to several months after the initiation of anti-tuberculosis treatments. 3,4 It is more frequent in patients with extrapulmonary or disseminated tuberculosis.…”
Section: Introductionmentioning
confidence: 99%